HRD Matrix: Understanding the Duality of Structure and Agency in Human Resource Development - Ali Asghari Sarem; حسن دانایی فرد; آرین قلی پور; علی اصغر فانی (مدیریت دولتی, 2017)
Achieving to human resource development (HRD) goals is depend on to match human and organization through learning. But there is a question, how we can match them and what is the role of agency and structure in this process? The purpose of this paper is to present a typology model in HRD. In this paper, the features of agency and structure of HRD, by using critical incident technique, were identified. Participants were consisted of Mapna company managers. The “HRD Matrix” have two dimensions or two strategic refrence points. In this paper we will identify four status in the HRD matrix that is created by these two strategic refrence point. The last but not least, we will explain and understand the duality of structure and agency in HRD.